Assessment of the mixed origin of the gastric epithelial extracellular vesicles in acellular transfer of Helicobacter pylori toxins and a systematic review. (April 2023) - Saberi, Samaneh; Esmaeili, Maryam; Saghiri, Reza; Shekari, Faezeh; Mohammadi, Marjan
Abstract: Background: H. pylori are generally considered as extracellular organisms, with exclusive colonization of the gastric milieu. Yet, several extra gastric manifestations are associated with this infection. The aim of the present study was to investigate the feasibility of toxin transfer by extracellular vesicles, from bacterial and epithelial origins. Methods: Tox-positive H. pylori and its two cagA and vacA mutant strains were used to produce bacterial vesicles (BVs) and to infect AGS cells. The produced BVs and the infected cell vesicles (ICVs) were collected by ultracentrifugation and evaluated by western blotting, DLS and electron microscopy. These two sets of vesicles were applied to a second set of recipient AGS cells, in which the acellular transfer of toxins, IL-8 production and downstream morphologic changes were assessed, by western blotting, ELISA and light microscopy, respectively. Results: The BVs were positive for H. pylori membrane markers (BabA and UreB), VacA and CagA toxins, except for from the corresponding mutant strains. The ICVs were larger in size and positive for bacterial markers, as well as epithelial markers of CD9, LGR5, but negative for nuclear (Ki76) or cytoplasmic (β-actin) markers. Bacteria-independent transfer of CagA and VacA into the recipient cells occurred upon treatment of cells with BVs and ICVs, followed by cellular vacuolation and elongation. IL-8 production was induced in recipient AGS cells, treated with BVs (1279.4 ± 19.79 pg/10 6  cells), early (8 h, 1171.4 ± 11.31 pg/10 6  cells) and late (48 h, 965.4 ± 36.77 pg/10 6  cells) ICVs ( P  < 0.0001). Conclusion: Our data indicates that ICVs, with mixed bacterial and epithelial constituents, similar to BVs, are capable of transferring bacterial toxins into the recipient cells, inducing IL-8 production and subsequent morphologic changes, in an acellular manner.